2012
DOI: 10.1155/2012/606195
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Roles of Ro/SSA Autoantibody System

Abstract: Anti-Ro/SSA antibodies are among the most frequently detected autoantibodies against extractable nuclear antigens and have been associated with systemic lupus erythematosus (SLE) and Sjögren's syndrome (SS). Although the presence of these autoantibodies is one of the criteria for the diagnosis and classification of SS, they are also sometimes seen in other systemic autoimmune diseases. In the last few decades, the knowledge of the prevalence of anti-Ro/SSA antibodies in various autoimmune diseases and symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 152 publications
(154 reference statements)
5
91
2
6
Order By: Relevance
“…The positive antibody rate to Ro in SLE and SS was reported to be 40-90 and 70-100%, which is in accordance with the various damages associated with these disorders (Yoshimi et al, 2012). Its antigens included 60-and 52-kDa nucleoproteins.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The positive antibody rate to Ro in SLE and SS was reported to be 40-90 and 70-100%, which is in accordance with the various damages associated with these disorders (Yoshimi et al, 2012). Its antigens included 60-and 52-kDa nucleoproteins.…”
Section: Introductionsupporting
confidence: 62%
“…BALB/c mice immunized with different degrees of oxidative modification of Ro60 (representing different epitopes modified) induced animals different spectrum of damages similar to that seen in patients with SLE and SS, which revealed that Ro60 autoantibodies might play an important role in the pathogenesis of the diseases and in the clinical damage seen in SLE and pSS (Kurien et al, 2011). In addition, clinical research has shown that the LC decrease observed in patients with pSS was related to the presence of Ro autoantibodies (Yoshimi et al, 2012). To investigate the possible role of autoantibodies to the various epitopes of Ro60 in the LC decrease in these different diseases, we selected Ro60 antibodies positive patients with SLE and pSS who exhibited LC decrease as subjects.…”
Section: Discussionmentioning
confidence: 87%
“…Dysfunction of T cells and accelerated activation of B cells in SLE patients [4] enables the development of various autoantigens such as the anti-nuclear antibody [5]. SLE specific autoantibodies thus far reported were the anti-Sm antibody [6], anti-double-stranded DNA antibody [7], anti-U1RNP antibody [8], anti-SSA/Ro antibody [9,10] and the anti-P ribosomal protein antibody [11], yet the pathogenic role of these antibodies remains to be proven. Accelerated atherosclerotic diseases have been recognized as major causes of mortality in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…3 The condition is nine times more common among women than among men, with peak onset during menopause. 1 A recent review suggests that the prevalence ranges from 0.1% to 4.8%, 1 with rates increasing with advanced age.…”
mentioning
confidence: 99%
“…Antibodies against La/SSB are considered to be a highly specific diagnostic marker for Sjögren syndrome. 3,56 According to the classification criteria, the presence of these antibodies along with other features suggestive of Sjögren syndrome is sufficient for establishing the diagnosis, even in the absence of a positive salivary gland biopsy. 57 Once the diagnosis is established, additional investigational tests (e.g., cryoglobulins, complement levels, immunofixation) should also be offered, particularly to patients with peripheral purpura, peripheral neuropathy, salivary gland enlargement or in situ demonstration of salivary gland lymphoma.…”
mentioning
confidence: 99%